The Effectiveness of the SISKA Application's One-Stop Service Management in New Student Admissions at UM Buton - Basri; Muhamad Ridwan; Jufri; Raju; Alimudin; Tarno (AIQU: Journal Multidiscipliner of Science, 2025)
This study aims to analyze the management of the Campus One-Stop Service Information System (SISKA) application in supporting the admission services for new students (PMB) at Universitas Muhammadiyah Buton. The background of this research is based on the importance of digitalizing higher education services to improve efficiency, transparency, and convenience for prospective students. This research employs a qualitative approach with data collection techniques including direct observation, in-depth interviews, and documentation. The study was conducted at the PMB Unit of UM Buton. The results indicate that the SISKA application has significantly simplified the new student admission process online, from uploading documents and filling out personal data to selecting study programs. However, its implementation still faces several challenges, such as low digital literacy among some applicants, the absence of a user guidance feature, and technical difficulties in uploading documents. The discussion is based on public service management theory and is supported by previous studies emphasizing the role of digital literacy in utilizing online-based service systems. The conclusion of this study is that the SISKA application has significantly supported the one-stop service management system, although improvements in user education and feature enhancement are needed to make the system more inclusive and effective in future implementation.